PENINGKATAN PENGETAHUAN INFEKSI MENULAR SEKSUAL DAN HIV/AIDS DENGAN PENDEKATAN CERAMAH PADA PELAJAR SMPN DI KOTA PALEMBANG - Putri Mahirah Afladhanti; Pariyana Pariyana; Eka Handayani Oktharina (As-Sidanah, 2023)
Sexually Transmitted Infections commonly abbreviated as STIs are caused by various types of microorganisms that are usually transmitted through sexual contact. Palembang is the largest contributor of STI and HIV/AIDS cases in South Sumatra. A lecture and discussion with a PowerPoint presentation and posters were used to carry out this community service project. This activity aimed to determine the increase in knowledge about STI and HIV/AIDS after health education for junior high school students in Palembang. A pre-and post-test questionnaire containing ten questions was utilized as the evaluation instrument. According to the frequency distribution of participants' knowledge before health education, 59.5% were in the category of moderate knowledge. In the meantime, after receiving health education, the participants' knowledge improved to 33.3% in the moderate category and 64.3% in the good category. Based on the mean score after health education, the value was 10.48 points greater than before health education with a p-value of 0.00. This health education about STI and HIV/AIDS can significantly improve the knowledge of participants. The most important thing in this community service was to educate students to prevent this disease, thus reducing the stigma and prevalence of these diseases.